2014
DOI: 10.1172/jci73015
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase WIP1 regulates adult neurogenesis and WNT signaling during aging

Abstract: The number of newly formed neurons declines rapidly during aging, and this decrease in neurogenesis is associated with decreased function of neural stem/progenitor cells (NPCs). Here, we determined that a WIP1-dependent pathway regulates NPC differentiation and contributes to the age-associated decline of neurogenesis. Specifically, we found that WIP1 is expressed in NPCs of the mouse subventricular zone (SVZ) and aged animals with genetically enhanced WIP1 expression exhibited higher NPC numbers and neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
59
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 24 publications
9
59
0
Order By: Relevance
“…Aged SVZ NSPCs form smaller neurospheres and adherent colonies compared with young adult NSPCs, and this correlates with their decreased proliferation capacity in vitro (Ahlenius et al., 2009; Corenblum et al., 2016; Daynac et al., 2014, 2016; L'Episcopo et al., 2013; Zhu et al., 2014). We also observed a proliferation defect in NSPCs derived from the aged mice (Figures S1B,C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aged SVZ NSPCs form smaller neurospheres and adherent colonies compared with young adult NSPCs, and this correlates with their decreased proliferation capacity in vitro (Ahlenius et al., 2009; Corenblum et al., 2016; Daynac et al., 2014, 2016; L'Episcopo et al., 2013; Zhu et al., 2014). We also observed a proliferation defect in NSPCs derived from the aged mice (Figures S1B,C).…”
Section: Resultsmentioning
confidence: 99%
“…Aging is associated with reduced neurogenesis in the mouse SVZ and SGZ (Encinas et al., 2011; Enwere et al., 2004; Lugert et al., 2010; Luo, Daniels, Lennington, Notti & Conover, 2006), which might lead to decreased olfactory function and cognitive hippocampus‐dependent impairment (Goncalves et al., 2016; Lledo & Valley, 2016). This age‐associated neurogenic decline appears to be caused both by a depletion in the NSPC pool of the aged niche (Ahlenius, Visan, Kokaia, Lindvall & Kokaia, 2009; Bouab, Paliouras, Aumont, Forest‐Berard & Fernandes, 2011; Corenblum et al., 2016; Enwere et al., 2004; Luo et al., 2006; Maslov, Barone, Plunkett & Pruitt, 2004; Molofsky et al., 2006; Stoll et al., 2011) and by the decreased capacity of the remaining NSPCs to sustain proliferation and neuronal differentiation, as revealed by in vitro studies (Ahlenius et al., 2009; Apostolopoulou et al., 2017; Corenblum et al., 2016; Daynac, Morizur, Chicheportiche, Mouthon & Boussin, 2016; Daynac et al., 2014; L'Episcopo et al., 2013; Shi et al., 2017; Zhu et al., 2014). NSPCs undergo cell autonomous age‐related changes that affect intracellular molecular pathways, including the altered expression of telomerase and cell cycle regulators, which have been linked to the decline in NSPC proliferation upon aging (Caporaso, Lim, Alvarez‐Buylla & Chao, 2003; Molofsky et al., 2006; Nishino, Kim, Chada & Morrison, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Wip1 expression has been shown to decrease with age in pancreatic islets and in neural stem/progenitor cells 23,26 . To examine the expression levels of Wip1 mRNA in HSCs and HPCs, we purified long-term (LT) HSCs, short-term (ST) HSCs, multipotent progenitors and lineage-committed progenitors (common lymphoid progenitors; common myeloid progenitors; megakaryocyte-erythroid progenitors; and granulocyte-macrophage progenitors) from young (2-to 3-month-old) and old (20-to 24-month-old) WT mice via fluorescence-activated cell sorting (FACS), as depicted in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In pancreatic islets, reduced Wip1 expression contributes to the aging-related decline in the proliferation and regenerative capacities of pancreatic islets via increased p38 activity 26 . In the subventricular zone, decreased Wip1 expression contributes to neuron formation defects via increased DKK3 activity, which inhibits the Wnt signalling pathway 23 . Our study showed that Wip1 expression progressively reduces with age in HSCs and Wip1 deletion accelerates HSC aging by increasing p53 and mTORC1 activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation